Autonomous attendance monitoring system / Mohamad Iqmal Ussaiq Ismail ...[et al.] - Ismail, Mohamad Iqmal Ussaiq; Ahmad Dzarawi, Muhamad Hakim; Md Azman, Muhamad Alif Zhafri; Mohamad Rosman, Mohamad Rahimi; Mohd Salleh, Mohd Idzwan (Universiti Teknologi Mara Kelantan, 2020)
Absenteeism is an act of habitual absence from work or schools. Absenteeism is considered as one of the worst social problem that may lead into another social problems, such as theft, drug, and bullying. Chronic absenteeism affects the performance of the individual; as well as those around them. In the context of Malaysian, Ministry of Education recorded that more than 37, 000 students were found absence from schools in the year 2017. Recent survey on the similar issue within the university context show that approximately 15 students were barred from examination due to poor attendance. Henceforth, there is a need for a new mechanism to replaced conventional attendance taking method. Therefore, Autonomous Attendance Monitoring System (AMoS) was developed in three stages. First, a qualitative study was conducted to investigate the problem with attendance monitoring. Then, the prototype of AMoS was developed based on PHP programming language, MySQL database, HTML5, CSS3, and jQuery. Lastly, a quantitative study was conducted to measure the extent of user satisfaction towards using AMoS. In term of novelty, AMoS improved the current absenteeism workflow implemented at UiTM, introduce new novel ideas of autonomous YY-ZZ monitoring, and a new absenteeism scale Ami-X. The system can be commercialized to any organization, such as academic institution; kindergarten, schools, universities, boarding schools, etc. The prototype of AMoS is protected by Copyright Act 1987, and available online at Google Play Store